Remote Sensor Network Application For Monitoring System and Air Quality Classificatio - Ace, Albern; Rio, Almero (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2020)
Indonesia is one of the nations putting resources into the modern area. Businesses influence the climate, outstandingly air quality. On the off chance that the air contamination ousted by modern fireplaces couldn't be handled appropriately, it would unfavorably influence human wellbeing. As of now, checking the air quality in certain zones just uses one apparatus. This is esteemed insufficient to depict the state of air quality in a given region. Then again, introducing more than one device would be extravagant. This exploration applied the idea of remote sensor organization (WSN) for air quality checking by introducing more than one sensor hubs in a specific area and one sink that demonstrations to gather information from the sensor hubs at that point sends them to the worker. Air quality information acquired by the sensor hubs were then ordered utilizing the grouping technique in information mining that is k-closest neighbor (K-NN). Preceding grouping utilizing K-NN, information standardization was performed, which creates a decimal scaling with great execution for air quality information. The k esteems utilized for the K-NN characterization are 5. The exactness of the framework is 94.28%, the accuracy is 85.16% and the review is 93.35%.